Development and testing of a tree lopping machine as an attachment to the power tiller - JYOTHIRAJ C. R; Naushad A; Sujith George; Er. Jayan P. R (Guide) (Tavanur 1997 Department of Farm Power Machinery and Energy)
Development and testing of a tree lopping machine as an attachment to the power tiller
Development and testing of a tree lopping machine as an attachment to the power tiller